Exploring DNA-interaction and molecular structure of ruthenium/1,2-bis-(diphenylphosphino)ethane)-based complex - Campideli, Victor Cardoso; Montilla-Suárez, Jerica Margely; Silva, Tiago Almeida; Sicupira, Dalila Chaves; Oliveira, Katia Mara; Correa, Rodrigo Souza (European Journal of Chemistry, 2023)
The mixture of cis and trans-[RuCl2(dppe)2] (dppe: 1,2-bis-(diphenylphosphino)ethane) was prepared and the interaction with CT-DNA was evaluated by several methods, including UV-vis DNA spectroscopic titration, viscosity, and electrochemical studies. Investigation suggests that [RuCl2(dppe)2] interacts moderately with CT-DNA. Interestingly, the cis- and trans-isomers interact differently with DNA, as proved by the square-wave voltammetry studies. Finally, the crystal structure of trans-[RuCl2(dppe)2]Cl was obtained from an electrochemical solution and studied in detail, which presents a distorted octahedral geometry and interatomic parameters different from those found in the trans-[RuCl2(dppe)2] complex. Crystal data for C52H48Cl4P4Ru: triclinic, space group P-1 (no. 2), a = 9.240(3) Å, b = 10.9290(18) Å, c = 11.993(3) Å, α = 78.707(11)°, β = 86.712(13)°, γ = 82.598(13)°, V = 1177.1(5) Å3, Z = 1, T = 293(2) K, μ(MoKα) = 0.732 mm-1, Dcalc = 1.467 g/cm3, 8434 reflections measured (6.934° ≤ 2Θ ≤ 51.986°), 4607 unique (Rint = 0.0973, Rsigma = 0.1171) which were used in all calculations. The final R1 was 0.0537 (I > 2σ(I)) and wR2 was 0.1347 (all data).